Um aporte à sustentabiblidade hídrica da cidade de Uberaba por meio de atos legais pró-ativos - Barbosa, Ana Keila Andrade (2006)
The historical evolutions of the Brazilian environmental legislation and the environmental legal thought had followed the society development in relation to the environmental questions. Considering this estimative, this thesis observed the scarcity and/or hydrics resources degradation, recognizing that the water is "the most precious thing of the millennium", putting this question in the geographic and the legal debates. Hydrics Basin of the Uberaba River is fragile; thus the degradation materialized in the withdrawing of the vegetal covering for wood commercialization, agricultural pastures, plantation with agrochemical, soil and the hydrics resources badly use, it was considered as objective of this work to contribute for the preservation and/or the recovery of the municipal hydrics resource, by measures able to assure the water sustainable use. This intention is materialized in the suggestion of a pro-active legal instrument that makes possible the better handling of the hydrics resources supplied by the Uberaba River. For this, we did data-collecting in the draining area of the Uberaba River, based on bibliographical research in an ample quantity of magazines, books, environmental impacts analyses and its consequences about the hydrics outflow reduction. Moreover, we ve used the SIG through Erdas 8,5 software, without supervision, seeming to collect a bigger number of environmental-impacts data and, finally, to develop an pro-active law in the search of the hydrics sustainability of the Uberaba River Basin. The contribution of this thesis is to collaborate with the effectuation of the environmental norms, in form to guarantee a balanced environment , with basis in the environment principles, to the next generation, measure which is materialized in the proactive Law, for hydrical sustainability of the Uberaba River, proposed for this thesis.